Design considerations for the semi-digital hadronic calorimeter (SDHCAL) for future leptonic colliders. (29th July 2016) - Pingault, A.
Abstract: The first technological SDHCAL prototype having been successfully tested, a new phase of R&D, to validate completely the SDHCAL option for the International Linear Detector (ILD) project of the International Linear Collider (ILC), has started with the conception and the realisation of a new prototype. The new one is intended to host few but large active layers of the future SDHCAL. The new active layers, made of Glass Resistive Plate Chambers (GRPC) with sizes larger than 2 m 2 will be equipped with a new version of the electronic readout, fulfilling the requirements of the future ILD detector. The new GRPC are conceived to improve the homogeneity with a new gas distribution scheme. Finally the mechanical structure will be achieved using the electron beam welding technique. The progress realised will be presented and future steps will be discussed.